Nano-barium titanate and its preparation method, evaluation method and application
By regulating the hydrothermal reaction process of barium titanate, two-stage insulation method and post-treatment steps were used to solve the problem of defects in the preparation of barium titanate, and low-defect nanobarium titanate was prepared, which improved the performance of multi-layer ceramic capacitors.
Patent Information
- Application Number
- CN202410731673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The prior art is difficult to avoid surface or lattice defects when preparing barium titanate, resulting in high-quality use.
By regulating the hydrothermal reaction process of barium titanate, two-stage insulation methods are adopted: the first stage is 160℃-200℃, with a time of 6h-18h; the second stage is 200℃-240℃, with a time of 18h-30h. Combined with the post-treatment steps of solid-liquid separation, washing, drying and grinding, low-defect nanobarium titanate is prepared.
The preparation of low-defect nanobarium titanate is achieved, and the high voltage resistance and breakdown strength of multi-layer ceramic capacitors are improved.
Smart Images

Figure CN118744998B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic nanomaterials, and in particular to nano barium titanate and a preparation method, an evaluation method and an application thereof. Background Art
[0002] Barium titanate, as an electronic ceramic material with excellent performance, is one of the main raw materials for preparing multilayer ceramic capacitors (MLCC). At present, the development demand for thinner dielectric layers and higher reliability of MLCC has put forward higher requirements for barium titanate, and the preparation of defect-free or low-defect nano-barium titanate powder is one of the key technologies to achieve thinner dielectric layers and higher reliability of MLCC.
[0003] At present, the main methods for preparing barium titanate are solid phase method and hydrothermal method. The solid phase method is generally used to prepare medium and low-end products with larger particle size (≥300nm) or low requirements. The hydrothermal method is generally used to prepare products with smaller particle size (≤300nm).
[0004] The hydrothermal method for preparing barium titanate is to mix a certain form of barium source and titanium source, transfer them into a high-pressure reactor, and react to form barium titanate after heating to a certain temperature. This method is a bottom-up method for preparing barium titanate. The reaction process involves the nucleation and growth of barium titanate, and this process will inevitably introduce surface or lattice defects, resulting in the barium titanate being unable to be used with high quality.
[0005] Based on the above problem, the present invention proposes a method for preparing defect-free or low-defect nano-barium titanate by regulating the reaction process of barium titanate.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide nano barium titanate and its preparation method, evaluation method and application, and to prepare low-defect nano barium titanate by regulating the preparation process of barium titanate.
[0008] The present invention is achieved in that:
[0009] In the first aspect, the present invention provides a nano-barium titanate. A potassium bromide tablet containing nano-barium titanate is tested by Fourier infrared spectrometer. In the infrared spectrum obtained, the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 The intensity of the peaks at are all less than 5%, and the content of nano-barium titanate in the potassium bromide tablets is 10 mg / g.
[0010] In an optional embodiment, the purity of the barium titanate is ≥ 99%;
[0011] And / or, the average particle size of the nano-barium titanate is 60nm-300nm.
[0012] In a second aspect, the present invention provides a method for preparing the nano-barium titanate described in the aforementioned embodiment, comprising:
[0013] Hydrothermal reaction, mixing the titanium source suspension and the barium source solution to obtain a reaction solution, and heat-insulating the reaction solution in two stages to obtain a hydrothermal reaction product, wherein the first stage heat-insulating temperature is 160° C.-200° C., the time is 6 h-18 h, and the second stage heat-insulating temperature is 200° C.-240° C., the time is 18 h-30 h;
[0014] Post-processing: solid-liquid separation, washing, drying and grinding of the hydrothermal product to obtain the nano-barium titanate.
[0015] In an optional embodiment, the titanium source suspension includes a titanium source, a solvent and a dispersant;
[0016] Preferably, the dispersant is one or both of polycarboxylate and polyacrylate;
[0017] Preferably, the mass ratio of the dispersant to the titanium source is (0.001-0.005):1;
[0018] Preferably, at 25°C, the viscosity of the dispersant is 2000 mm 2 / s-10000mm 2 / s;
[0019] In an optional embodiment, the solvent is at least one of water and ethanol.
[0020] In an optional embodiment, the molar ratio of barium element to titanium element in the reaction solution is 1.1-3.0;
[0021] And / or, the titanium source is titanium dioxide;
[0022] And / or, the titanium source has a specific surface area of 10m 2 / g-110m 2 / g;
[0023] And / or, the barium source is barium hydroxide.
[0024] In an optional embodiment, during the hydrothermal reaction, the temperature of the reaction solution rises at a rate of 3°C / min-7°C / min.
[0025] In an optional embodiment, the washing step includes water washing, ethanol washing and glacial acetic acid solution washing, and the washing step is stopped when the pH of the washing solution is 7-8.
[0026] In an optional embodiment, the nano-barium titanate is further calcined after grinding, with the calcination temperature being 900° C.-1100° C. and the time being 1 h-3 h to obtain the nano-barium titanate with hydroxyl defects removed.
[0027] In a third aspect, the present invention provides an application of the nano-barium titanate described in the aforementioned embodiment in a multilayer ceramic capacitor.
[0028] In a fourth aspect, the present invention provides a method for evaluating nano-barium titanate according to the aforementioned embodiment, comprising the following steps: using a Fourier transform infrared spectrometer to test a potassium bromide tablet containing nano-barium titanate, and obtaining an infrared spectrum, wherein the content of nano-barium titanate in the potassium bromide tablet is 10 mg / g;
[0029] If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensities of the peaks at the positions are all less than or equal to the preset values, the nano barium titanate is a qualified product;
[0030] If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensity of the peaks at the locations is greater than the preset value, the nano-barium titanate is an unqualified product;
[0031] The preset value is less than 5%.
[0032] The present invention has the following beneficial effects:
[0033] The present invention provides a low-defect nano-barium titanate, which is applied to multilayer ceramic capacitors and is beneficial to improving the high voltage resistance and breakdown strength of multilayer ceramic capacitors. The low-defect nano-barium titanate is prepared by two stages of heat preservation, wherein the first stage of heat preservation temperature is 160°C-200°C, and the hydrothermal reaction at a lower temperature can regulate the ion diffusion energy, ensure the orderly arrangement of the diffused ions in the lattice, and complete the nucleation and growth of the grains; the second stage of heat preservation temperature is 200°C-240°C, at this stage, the grains can be further crystallized, and the low-defect nano-barium titanate is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is the infrared spectrum of the barium titanate powder prepared in Example 1;
[0036] Figure 2 This is the infrared spectrum of the barium titanate powder prepared in Comparative Example 1;
[0037] Figure 3 This is the infrared spectrum of the barium titanate powder prepared in Comparative Example 2;
[0038] Figure 4 This is the infrared spectrum of the barium titanate powder prepared in Comparative Example 3. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0040] The embodiment of the present invention provides a nano-barium titanate. A potassium bromide tablet containing nano-barium titanate is tested by Fourier infrared spectrometer. In the infrared spectrum obtained, the wave number 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1The intensity of the peaks at are all <5%, specifically can be 4.9%, 4.5%, 4%, 3.5%, 2%, 1%, 0 or any value <5%, and the content of nano-barium titanate in the potassium bromide tablet is 10 mg / g.
[0041] In the embodiment of the present invention, the intensity of the peak refers to the difference between the transmittance corresponding to the peak top and the transmittance corresponding to the peak bottom in the infrared spectrum; the test sample involved in the present invention is a potassium bromide tablet containing nano-barium titanate, which is obtained by mixing and grinding nano-barium titanate and potassium bromide and then pressing them into tablets.
[0042] In an optional embodiment, the purity of the barium titanate is ≥ 99%;
[0043] And / or, the average particle size of the nano-barium titanate is 60nm-300nm.
[0044] The present invention also provides a method for preparing the nano-barium titanate described in the above embodiment, comprising:
[0045] Hydrothermal reaction, mixing the titanium source suspension and the barium source solution to obtain a reaction solution, and heat-insulating the reaction solution in two stages to obtain a hydrothermal reaction product, wherein the first stage heat-insulating temperature is 160° C.-200° C., the time is 6 h-18 h, and the second stage heat-insulating temperature is 200° C.-240° C., the time is 18 h-30 h;
[0046] Post-processing: solid-liquid separation, washing, drying and grinding of the hydrothermal product to obtain the nano-barium titanate.
[0047] In an embodiment of the present invention, nano-barium titanate is prepared by two stages of heat preservation, wherein the first stage heat preservation temperature is 160°C-200°C. Hydrothermal reaction at a lower temperature can regulate the ion diffusion energy, ensure the orderly arrangement of diffused ions in the lattice, and complete the nucleation and growth of grains; the second stage heat preservation temperature is 200°C-240°C. At this stage, the grains can be further crystallized to prepare low-defect nano-barium titanate.
[0048] In an optional embodiment, the titanium source suspension includes a titanium source, a solvent and a dispersant;
[0049] The titanium source suspension includes a dispersant. The electrostatic adsorption characteristics of the dispersant are utilized to allow the dispersant to be relatively evenly wrapped on the surface of the titanium source, thereby regulating the diffusion rate of the titanium source in the hydrothermal process, which is beneficial to reducing the defects of the prepared nano-barium titanate.
[0050] In an optional embodiment, the dispersant is one or both of polycarboxylate and polyacrylate;
[0051] In an optional embodiment, the mass ratio of the dispersant to the titanium source is (0.001-0.005):1. Excessive use of the dispersant will inhibit the diffusion of the titanium source and increase the defects of the prepared nano-barium titanate.
[0052] Preferably, at 25°C, the viscosity of the dispersant is 2000 mm 2 / s-10000mm 2 / s, too high viscosity will reduce the diffusion rate of the titanium source during the hydrothermal reaction, and too low viscosity will be unfavorable for the dispersant to wrap the titanium source.
[0053] In an optional embodiment, the solvent is at least one of water and ethanol. In some embodiments, a mixed solution of water and ethanol is used as the solvent, wherein the volume ratio of water to ethanol can be 1:(1-0.1). The presence of the solvent is conducive to uniform mixing of the dispersant titanium source. In some embodiments, the concentration of the titanium source in the titanium source suspension is 1-2 mol / L.
[0054] In an optional embodiment, the molar ratio of barium element to titanium element in the reaction solution is 1.1-3.0, and excess barium is beneficial to the forward reaction and reduces the inclusion of titanium source in barium titanate.
[0055] In an alternative embodiment, the titanium source is titanium dioxide.
[0056] In an optional embodiment, the titanium source has a specific surface area of 10 m 2 / g-110m 2 / g, the larger the specific surface area of the titanium source, the smaller the particle size of the prepared nano-barium titanate.
[0057] In an alternative embodiment, the barium source is barium hydroxide.
[0058] It should be noted that the barium source solution includes a barium source and water. Since the barium source, such as barium hydroxide, is difficult to dissolve, in some embodiments, the preparation method of the barium source solution includes the following steps: quantitatively weighing barium hydroxide and water, adding them to a hydrothermal reactor, heating to 80-120°C and keeping warm for 1-3 hours, so that the barium hydroxide is fully dissolved to obtain a barium source solution.
[0059] In an optional embodiment, during the hydrothermal reaction, the temperature of the reaction solution rises at a rate of 3°C / min-7°C / min.
[0060] In an optional embodiment, the washing step includes water washing, ethanol washing and glacial acetic acid solution washing, and the washing step is stopped when the pH of the washing solution is 7-8.
[0061] In an optional embodiment, the nano-barium titanate is further calcined after grinding, the calcination temperature is 900° C.-1100° C., and the time is 1 h-3 h to obtain nano-barium titanate with hydroxyl defects removed. Calcination is beneficial to remove the hydroxyl groups present in the nano-barium titanate.
[0062] The embodiment of the present invention also provides an application of the nano-barium titanate described in the above embodiment in a multilayer ceramic capacitor. The use of low-defect nano-barium titanate in a multilayer ceramic capacitor is beneficial to improving the high voltage resistance and breakdown strength of the multilayer ceramic capacitor.
[0063] The embodiment of the present invention further provides an evaluation method of the nano-barium titanate described in the above embodiment, comprising the following steps: using a Fourier infrared spectrometer to test a potassium bromide tablet containing nano-barium titanate, and obtaining an infrared spectrum, wherein the content of nano-barium titanate in the potassium bromide tablet is 10 mg / g;
[0064] If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensities of the peaks at the positions are all less than or equal to the preset values, the nano barium titanate is a qualified product;
[0065] If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensity of the peaks at the locations is greater than the preset value, the nano-barium titanate is an unqualified product;
[0066] The preset value is less than 5%.
[0067] The applicant has found that the number of surface or lattice defects in nano-barium titanate is related to the 1250-1050cm -1 The peak intensity in the low-intensity range is related to the peak intensity of the potassium bromide tablet containing nano-barium titanate at wave number 1210 cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 That is, the more surface or lattice defects there are in nano-baTiO3, the higher the wave number is.-1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 The stronger the peak intensity, the fewer surface or lattice defects in the nano-barium titanate. The wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 Therefore, in the infrared spectrum of nano-barium titanate in the embodiment of the present invention, the wave number 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 The intensity of the peak at is used to evaluate the quality of nano-barium titanate.
[0068] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0069] Embodiment 1:
[0070] This embodiment provides a method for preparing nano-barium titanate, comprising the following steps:
[0071] (1) Weigh 14 mol of barium hydroxide octahydrate and transfer it into a hydrothermal reactor filled with 8 L of water, seal it, place it in a high-temperature reaction box, raise the temperature to 90° C. and keep it warm for 2 h.
[0072] (2) Prepare titanium source suspension: 7 mol of titanium dioxide, with a specific surface area of 30 m 2 / g, the volume of pure water and ethanol are 4L and 4L respectively, and the dispersant is: 1.1186g polycarboxylate (viscosity 6000mm 2 / s). After the insulation of step (1) is completed, the titanium source suspension is transferred to the hydrothermal reaction kettle of step (1), and placed in a high-temperature reaction box, and the hydrothermal reaction insulation system is set: the first stage temperature: 180°C, insulation for 12h; the second stage temperature: 220°C, insulation for 24h.
[0073] (3) After the reaction is completed, the hydrothermal product in step (2) is collected, washed, dried, and ground to obtain the target barium titanate powder.
[0074] Embodiment 2:
[0075] This embodiment provides a method for preparing nano-barium titanate, comprising the following steps:
[0076] (1) Weigh 14 mol of barium hydroxide octahydrate and transfer it into a hydrothermal reactor filled with 8 L of water, seal it, place it in a high-temperature reaction box, and heat it to 80° C. for 3 h.
[0077] (2) Prepare titanium source suspension: the titanium dioxide content is 12.72 mol, and the specific surface area of titanium dioxide is 110 m 2 / g, pure water volume is 7L, 1L, dispersant is: 5.0816g polycarboxylate (viscosity 2000mm 2 / s). After the insulation of step (1) is completed, the titanium source suspension is transferred to the hydrothermal reaction kettle of step (1), and placed in a high-temperature reaction box, and the hydrothermal reaction insulation system is set: the first stage temperature: 180°C, insulation for 6 hours; the second stage temperature: 210°C, insulation for 36 hours.
[0078] (3) After the reaction is completed, the hydrothermal product in step (2) is collected, washed, dried, ground, and calcined to obtain the target barium titanate powder.
[0079] Embodiment 3:
[0080] This embodiment provides a method for preparing nano-barium titanate, comprising the following steps:
[0081] (1) Weigh 14 mol of barium hydroxide octahydrate and transfer it to a hydrothermal reactor filled with 8 L of water, seal it, place it in a high-temperature reaction box, raise the temperature to 100 °C and keep it warm for 1 h.
[0082] (2) Prepare titanium source suspension: 9.3 mol of titanium dioxide, with a specific surface area of 80 m 2 / g, the volume of pure water and ethanol are 6L and 2L respectively, and the dispersant is: 2.2292g polyacrylate (viscosity 5000mm 2 / s). After the insulation of step (1) is completed, the titanium source suspension is transferred to the hydrothermal reaction kettle of step (1), and placed in a high-temperature reaction box, and the hydrothermal reaction insulation system is set: the first stage temperature: 160°C, insulation for 18h; the second stage temperature: 230°C, insulation for 18h.
[0083] (3) After the reaction is completed, the hydrothermal product in step (2) is collected, washed, dried, and ground to obtain the target barium titanate powder.
[0084] Embodiment 4:
[0085] This embodiment provides a method for preparing nano-barium titanate, comprising the following steps:
[0086] (1) Weigh 14 mol of barium hydroxide octahydrate and transfer it to a hydrothermal reactor filled with 8 L of water, seal it, place it in a high-temperature reaction box, and heat it to 90° C. and keep it warm for 2 h.
[0087] (2) Prepare titanium source suspension: 4.66 mol of titanium dioxide, with a specific surface area of 10 m 2 / g, the volumes of pure water and ethanol are 7.2L and 0.8L respectively, and the dispersant is: 0.27923g polycarboxylate (viscosity 10000mm 2 / s) and 0.27923g polyacrylate (viscosity 6000mm 2 / s). After the insulation of step (1) is completed, the titanium source suspension is transferred to the hydrothermal reaction kettle of step (1), and placed in a high-temperature reaction box, and the hydrothermal reaction insulation system is set: the first stage temperature: 200°C, insulation for 12h; the second stage temperature: 240°C, insulation for 24h.
[0088] (3) After the reaction is completed, the hydrothermal product in step (2) is collected, washed, dried, and ground to obtain the target barium titanate powder.
[0089] Embodiment 5:
[0090] This embodiment provides a method for preparing nano-barium titanate, comprising the following steps:
[0091] (1) Weigh 14 mol of barium hydroxide octahydrate and transfer it to a hydrothermal reactor filled with 8 L of water, seal it, place it in a high-temperature reaction box, and heat it to 90° C. and keep it warm for 2 h.
[0092] (2) Prepare titanium source suspension: 5.6 mol of titanium dioxide, with a specific surface area of 40 m 2 / g, the volume of pure water and ethanol were 5L and 3L respectively, and the dispersant was: 0.4474g polyacrylate (viscosity 10000mm 2 / s). After the insulation of step (1) is completed, the titanium source suspension is transferred to the hydrothermal reaction kettle of step (1), and placed in a high-temperature reaction box, and the hydrothermal reaction insulation system is set: the first stage temperature: 180°C, insulation for 12h; the second stage temperature: 220°C, insulation for 30h.
[0093] (3) After the reaction is completed, the hydrothermal product in step (2) is collected, washed, dried, and ground to obtain the target barium titanate powder.
[0094] Comparative Example 1:
[0095] This comparative example provides a method for preparing nano-barium titanate, which is different from Example 1 only in that no dispersant is added in step (2).
[0096] Comparative Example 2:
[0097] This comparative example provides a method for preparing nano-barium titanate, which is different from Example 1 only in that the hydrothermal reaction insulation system in step (2) is: 220° C., insulation for 30 h.
[0098] Comparative Example 3:
[0099] This comparative example provides a method for preparing nano-barium titanate, which is different from Example 1 only in that no dispersant is added in step (2), and the hydrothermal reaction is carried out at a temperature of 220° C. for 30 h.
[0100] Comparative Example 4
[0101] This comparative example provides a method for preparing nano-barium titanate, which is different from Example 1 only in that in step (2), the temperature in the first stage is too low, which is 140°C.
[0102] Comparative Example 5
[0103] This comparative example provides a method for preparing nano-barium titanate, which differs from Example 1 only in that, in step (2), the temperature of the second stage is too high, 260° C. When the temperature of the second stage is too high, the particle size of the barium titanate particles will grow and exceed the target particle size requirement. In addition, too large a particle size of the powder will also affect the voltage resistance of the ceramic disc.
[0104] Comparative Example 6
[0105] This comparative example provides a method for preparing nano-barium titanate, which differs from Example 1 only in that in step (2), the hydrothermal reaction is kept at 180°C for 36 hours. When the first stage keeping time is too long, there is no substantial improvement on the powder, resulting in energy waste.
[0106] Comparative Example 7
[0107] This comparative example provides a method for preparing nano-barium titanate, which differs from Example 1 only in that in step (2), the hydrothermal reaction is kept at 220°C for 36 hours. When the second stage keeping time is too long, there is no substantial improvement on the powder, resulting in energy waste.
[0108] Comparative Example 8
[0109] This comparative example provides a method for preparing nano-barium titanate, which is different from Example 1 only in that in step (2), the amount of polycarboxylate used is 3.36 g.
[0110] The barium titanate powders prepared in the above examples and comparative examples were subjected to infrared testing. The results are shown in Table 1. The infrared test images of the barium titanate powders prepared in Example 1 and Comparative Examples 1-3 are shown in Table 1. Figure 1-4As shown, the content of barium titanate in the potassium bromide tablets used in the infrared test is 10 mg / g, and the testing equipment is a PE200 infrared spectrometer.
[0111] In addition, the barium titanate powder prepared in the above examples and comparative examples was made into a ceramic disc with a thickness of 1 mm, and its voltage resistance was tested as shown in Table 1, wherein the test method of voltage resistance is: DC voltage method: DC voltage method is a commonly used method for measuring the breakdown voltage of ceramics. This method determines the breakdown voltage by gradually increasing the DC voltage and observing whether the insulator breaks down.
[0112] Table 1
[0113]
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing nano barium titanate, characterized in that: include: Hydrothermal reaction, mixing the titanium source suspension and the barium source solution to obtain a reaction solution, and heat-insulating the reaction solution in two stages to obtain a hydrothermal reaction product, wherein the first stage heat-insulating temperature is 160° C.-200° C., the time is 6 h-18 h, and the second stage heat-insulating temperature is 200° C.-240° C., the time is 18 h-30 h; Post-processing: solid-liquid separation, washing, drying and grinding of the hydrothermal product to obtain the nano-barium titanate; The potassium bromide tablet containing nano-barium titanate was tested by Fourier infrared spectrometer. The infrared spectrum obtained had a wave number of 1210 cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 The intensity of the peaks at are all less than 5%, and the content of nano-barium titanate in the potassium bromide tablets is 10 mg / g.
2. The method for preparing nano-barium titanate according to claim 1, characterized in that: The purity of the barium titanate is ≥99%; And / or, the average particle size of the nano-barium titanate is 60nm-300nm.
3. The method for preparing nano-barium titanate according to claim 1, characterized in that: The titanium source suspension comprises a titanium source, a solvent and a dispersant.
4. The method for preparing nano-barium titanate according to claim 3, characterized in that: The dispersant is one or both of polycarboxylate and polyacrylate.
5. The method for preparing nano-barium titanate according to claim 3, characterized in that: The mass ratio of the dispersant to the titanium source is (0.001-0.005):
1.
6. The method for preparing nano-barium titanate according to claim 3, characterized in that: At 25°C, the viscosity of the dispersant is 2000 mm 2 / s-10000mm 2 / s.
7. The method for preparing nano-barium titanate according to claim 3, characterized in that: The solvent is at least one of water and ethanol.
8. The method for preparing nano-barium titanate according to claim 1, characterized in that: The molar ratio of barium element to titanium element in the reaction solution is 1.1-3.0; And / or, the titanium source is titanium dioxide; And / or, the specific surface area of the titanium source is 10m 2 / g-110m 2 / g; And / or, the barium source is barium hydroxide.
9. The method for preparing nano-barium titanate according to claim 1, characterized in that: In the hydrothermal reaction, the temperature of the reaction solution rises at a rate of 3°C / min-7°C / min.
10. The method for preparing nano-barium titanate according to claim 1, characterized in that: The washing step includes water washing, ethanol washing and glacial acetic acid solution washing, and the washing step is stopped when the pH value of the washing solution is 7-8.
11. The method for preparing nano-barium titanate according to claim 1, characterized in that: After grinding, the nano-barium titanate is calcined at a temperature of 900° C. to 1100° C. for a time of 1 h to 3 h to obtain the nano-barium titanate with hydroxyl defects removed.
12. A method for evaluating nano-barium titanate prepared by the method according to any one of claims 1 to 11, characterized in that: The following steps are involved: The potassium bromide tablet containing nano-barium titanate was tested by Fourier infrared spectrometer, and the infrared spectrum obtained showed that the content of nano-barium titanate in the potassium bromide tablet was 10 mg / g; If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensities of the peaks at the positions are all less than or equal to the preset values, the nano barium titanate is a qualified product; If the wave number is 1210cm -1 -1215cm -1 、1112cm -1 -1116cm -1 、1069cm -1 -1073cm -1 If the intensity of the peaks at the locations is greater than the preset value, the nano-barium titanate is an unqualified product; The preset value is less than 5%.
Citation Information
Patent Citations
Low-temperature preparation method of high-tetragonal-phase-content nano barium titanate powder
CN105439196A
Preparation method of tetragonal phase nano barium titanate
CN111762810A